Transcriptome and proteome of the highly neurotoxic venom of Gloydius intermedius. (1st December 2015) - Yang, Zhang-Min; Yang, Yu-E.; Chen, Yu; Cao, Jing; Zhang, Cui; Liu, Ling-Ling; Wang, Zhe-Zhi; Wang, Xu-Min; Wang, Ying-Ming; Tsai, Inn-Ho
Abstract: The venomics of Gloydius intermedius were investigated using expressed sequence tags (ESTs) analyses, 2D gel-electrophoresis combined with MALDI-TOF/TOF, and LC-MS/MS. A total of 1920 ESTs from the venom gland cDNA library were sequenced; 74% of them belonged to toxin-families. The four most abundant families among the toxin transcripts were: serine protease (SP, 36.2%), bradykinin potentiating peptide (25.3%), l -amino acid oxidase (LAAO, 13.1%), and phospholipase A2 (PLA2, 9.9%). Moreover, the full sequences of four PLA2 s, eight SPs, cysteine-rich secretory protein (CRISP), C-type-lectin-like-protein (CTLP), hyaluronidase, metalloproteinase, and nerve growth factor were deduced from the cDNA sequences. Excluding the CRISP and hyaluronidase, most of the G. intermedius venom proteins bear 92–99% sequence identities to those of other pitviper venoms. The most abundant components are PLA2 s (37%), SPs (20%) and LAAO (6%), while metalloproteinase, CTLP, and other components each account for <3% of the total venom proteins. The abundance of Gintexin (a crotoxin-like neurotoxin) and low levels of hemorrhagic metalloproteases, disintegrins and CTLPs highlight the great venom differences between G. intermedius and other hemorrhagic pitvipers. The bimorphism of hemorrhagic and neurotoxic venoms among Gloydius is confirmed; our results shed more lights on the co-evolution of both neurotoxicity and hypotension in some viperid venoms. Graphical abstract: Highlights: Gloydius intermedius venom contains abundant crotoxin-like neurotoxins, kallikrein-like proteases and BPP. The venom gland ESTs reveal the most abundant venom families: SP > BPP > LAAO > PLA2 . Similarity between Gintexin and Crotoxin subunits supports G. intermedius being the Asian sister of neurotoxic rattlers. Co-evolution of neurotoxic and hypotensive toxins occurs in viperid venoms.